Intervensi Manajemen Perawatan Mandiri Penderita Stroke: Systematic Review - Heriviyatno Julika Siagian (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Stroke is the leading cause of death and disability globally. A number of studies have contributed to the knowledge base regarding self-management interventions among chronic disease patients, but there have been few studies for stroke patients. Therefore, it is necessary to analyze self-management interventions in stroke patients. This systematic review aims to identify and describe experimental studies related to self-management interventions for stroke survivors. This study follows the guidelines of the Preferred Reporting Item Systematic Review and Meta Analysis (PRISMA). Databases used include PubMed, Web of Science, Sciencedirect, Cochrane Central Register of Controlled Trials, and Willey online library. The search was conducted on articles published from 2000 to 2022. Two independent reviewers were asked to assess potential articles, and included data extraction for articles that met the criteria. Twenty one articles met the inclusion criteria. The most widely discussed study design is the comparison of self-management interventions with usual care. Physical activity was the most common topic of intervention, and the main intervention was delivered face-to-face. Interventions are carried out by various providers, including nurses as the most common provider group. Symptom management is the outcome domain most frequently reported as improving or improving. Self-care management interventions are very beneficial for the management of stroke patient symptoms. The duration of the intervention is at least 6-12 months. Various intervention topics, delivery methods, and service providers are used to a large extent to meet the various needs of stroke patients. Physical activity is the most popular topic in relevant studies.